Peran Literasi Digital Sebagai Jembatan Dalam Penguatan Pendidikan Karakter Siswa Sekolah Dasar di Era Revolusi Industri 4.0 - Putri Sofiatul Maola; Dinie Anggraeni Dewi; Rizky Saeful Hayat (PT. ALHAFI BERKAH INDONESIA, 2023)
This research aims to strengthen students' character education which has begun to diminish due to the globalization that continues to spread through the application of digital literacy. The use of technology such as the internet is easily accessed by various groups, giving rise to unhealthy internet. This research was conducted using a qualitative method through an analytical descriptive approach, where the theory or basis of discussion is taken from the results of literature studies such as books, articles and journals by also describing theories, findings, and other research materials obtained from reference materials to serve as the basis for research activities to develop a framework of thinking related to character education, digital literacy, and its role in the era of the industrial revolution 4.0. This research can be used as a reference for the world of education, namely teachers, especially in elementary schools in strengthening student character. The results of this study show that the role of digital media is very influential for students' lives so that it can be used as an alternative for strengthening character education in the era of the industrial revolution 4.0 as it is now. By paying attention to aspects of digital skills, knowledge of the use of technology and awareness to use technology as well as possible can develop norms and ethical values.